Vibration and β‐hydroxy‐β‐methylbutyrate treatment suppresses intramuscular fat infiltration and adipogenic differentiation in sarcopenic mice. Issue 2 (28th January 2020) - Wang, Jinyu; Cui, Can; Chim, Yu Ning; Yao, Hao; Shi, Liu; Xu, Jiankun; Wang, Jiali; Wong, Ronald Man Yeung; Leung, Kwok‐Sui; Chow, Simon Kwoon‐Ho; Cheung, Wing Hoi
Abstract: Background: Sarcopenia is an aging‐induced deterioration of skeletal muscle mass and function. Low‐magnitude high‐frequency vibration (LMHFV) was shown to improve muscle functions and β‐hydroxy‐β‐methylbutyrate (HMB) to increase muscle mass and strength. Muscle‐derived stem cells (MDSCs) are progenitor cells important for muscle regeneration. We hypothesized that LMHFV and HMB could retard sarcopenia by reducing fat infiltration through inhibiting adipogenesis in MDSCs. Methods: Senescence‐accelerated mouse P8 male mice were randomized into control (CTL), HMB, LMHFV (VIB), and combined (COM) groups. Interventions started at age of month 7 and assessed at 1, 2, and 3 months post‐intervention by densitometry, histology, and functional tests. In vitro, MDSCs isolated from gastrocnemius of senescence‐accelerated mouse P8 mice were characterized, randomized into CTL, VIB, HMB, and COM groups, and assessed by oil red O staining, mRNA, and protein expression. Results: At 2 months post‐intervention, percentage lean mass of HMB, VIB, and COM groups were significantly higher than CTL group. Twitch, tetanic, and specific tetanic forces of COM group were higher, while specific twitch force of both VIB and COM groups were higher. Grip strength of HMB, VIB, and COM groups were higher. Histologically, both VIB and COM groups presented lower oil red O area than CTL group. Type I muscle fibre in CTL group was higher than HMB, VIB, and COM groups. MDSC were detected in situ by immunofluorescence stain with stem cell antigen‐1 signals confirmed with higher β‐catenin expression in the COM group. The observations were also confirmed in vitro, MDSCs in the HMB, VIB, and COM groups presented lower adipogenesis vs. the CTL group. β‐Catenin mRNA and protein expressions were lower in the CTL group while their relationship was further validated through β‐catenin knock‐down approach. Conclusions: Our results showed that combined LMHFV and HMB interventions enhanced muscle strength and decreased percentage fat mass and intramuscular fat infiltration as compared with either treatment alone. Additive effect of LMHFV and HMB was demonstrated in β‐catenin expression than either treatment in MDSCs and altered cell fate from adipogenesis to myogenesis, leading to inhibition of intramuscular lipid accumulation. Wnt/β‐catenin signalling pathway was found to be the predominant regulatory mechanism through which LMHFV and HMB combined treatment suppressed MDSCs adipogenesis.